Invented spelling activities in kindergarten : the role of instructional scaffolding and collaborative learning - Albuquerque, Ana (2020)
There is considerable evidence on the connections between emergent literacy-related skills in preschool-age and successful reading and writing. The purpose of this double-designed experimental/descriptive study was to analyse the impact of invented spelling activities on kindergarten children’s spelling performance and to explore adult mediation and peer collaboration processes that occurred within a sample of intervention sessions. Data was collected with 52 participants divided into an experimental group and a control group who were submitted to a pre/post-test assessment. The global quantitative analysis revealed the strong impact of the intervention on children’s word spelling progress scores. The descriptive qualitative data of 2304 verbal interventions of a small-scale sample suggested that significant and diverse mediation scaffolding strategies were incorporated by the children in a shared dialogical learning approach. Our findings point to the need for delivering group interaction activities combining early literacy contents in kindergarten contexts as a vehicle for responding to the challenge of reading and writing acquisition at the beginning of schooling.